The Sterility of Allotriploid Fish and Fertility of Female Autotriploid Fish - Hu, Fangzhou; Fan, Jingjing; Qin, Qinbo; Huo, Yangyang; Wang, Yude; Wu, Chang; Liu, Qingfeng; Li, Wuhui; Chen, Xuan; Liu, Cao; Tao, Min; Wang, Shi; et al. (Frontiers in Genetics, 2019)
Based on the formation of an autotetraploid fish line (4nAUT, 4n=200; F2-F11) derived from the distant hybridization of female Carassius auratus red var. (RCC, 2n=100) × male Megalobrama amblycephala (BSB, 2n=48), we produced autotriploid hybrids (3nAUT) by crossing females of RCC with males of 4nAUT and allotriploid hybrids (3nALT) by crossing females of Cyprinus carpio (CC, 2n=100) with males of 4nAUT. The aim of this study was to comparatively investigate the reproductive characteristics of 3nALT and 3nAUT. We investigated morphological traits, chromosomal number, DNA content and gonadal development in 3nAUT and 3nALT. The results indictaed both 3nAUT and 3nALT possessed 150 chromosomes and were triploid hybrids. The females and males of 3nALT and males of 3nAUT had abnormal gonadal development and could not generate mature egg or sperm, but the females of 3nAUT had normal gonadal development and generated mature eggs at two years old. The females of 3nAUT generated different sizes of eggs, which fertilized with haploid sperm from RCC and formed viable diploid, triploid and tetraploid offspring. The formation of these two kinds of triploid hybrids provides an ideal model for studying the reproductive traits of triploid hybrids, which is of great value in animal reproductive biology.